Next Stop, Cold Lake: Patterns of Mobility, Military Brats and Oil-Patch Kids - Asselin, Gabriel (Anthropologica, 2014)
The French-speaking population of Cold Lake, Alberta, is mainly constituted by mobile individuals coming from two sectors: the oil industry and the Canadian military. Based on fieldwork in and around a French-only school in Cold Lake, this article explores the community impact of having such a mobile resident make-up. From the parents', educators' and most importantly from the children's perspective, I ask how these mobile families relate to the many communities to which they belong, how they see themselves and how they articulate their sense of belonging.